Hubungan antara Kredibilitas Tutor dengan Minat Belajar Peserta Didik di Bimbingan Belajar Sempoa di Jalan Panjaitan Simpang IV Pasar Batusangkar - Efri Yona; Syafruddin Wahid (Universitas Negeri Padang, 2018)
This research is based on the low learning interest of learners of learning abacus in batusangkar, allegedly lack of credibility of tutor in teaching and learning process. This study aims to find out how the relationship Between the credibility of tutors with interest in learning learning abacus in batusangkar.This study is a correlational quantitative research with a population of fifty students with a sample of threety five students where sampling was carried out using the stratified random sampling technique. To collect data used questioner technique and data collection tool in the form of questionnaire.The results showed that (1) the credibility of abacus tutoring tutors in batusangkar was not good, (2) the learning interest of abacus tutoring students in batusangkar was low, and (3) there was a significant relationship between the credibility of tutors and students' learning interest. Suggested tutors can increase credibility in teaching and learning process of learning abacus in batusangkar.Keywords: Credibility Tutor, Interest to Learn